Positioning the Patient: Normative Analysis of Electronic Patient Records - van der Ploeg, I. (Methods of Information in Medicine, 2003)
Objective: This paper aims to take the current ethical research on electronic patient records beyond the ethical-legal issues of privacy to include contemporary issues of the ‘politics of technology’ and ‘value sensitive design’.Methods: The paper employs an interpretive approach to analyze research on electronic patient records with concepts of the politics of technology and value sensitive design.Results and Conclusions: The broad development towards computerization of patient records lacks needed attention to the potential effects of such systems on the patients. This paper argues for a broader understanding of the normative aspects involved in the design and implementation of electronic patient records (EPRs). It suggests three supplemental dimensions for normative analysis of EPR design relevant to the position of the patient: presence, agency, and identity. These dimension are discussed and illustrated as concepts connecting ethical dimensions of patienthood with design features of EPRs.
Keywords: Electronic patient record; ethics; normative analysis; value sensitive design; patient centered approach